Analisis Kontribusi Dan Efektivitas Pajak Restoran Terhadap Pendapatan Asli Daerah Kota Banjarmasin - Resti Sylvianur; Eny Fahraty (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The purpose of this study is to (1) know the level of restaurant tax growth rateof the City of Banjarmasin (2) find out how much the contribution of restaurant tax tothe original income of Banjarmasin City (3) to find out how far the restaurant taxeffectiveness Banjarmasin City.The data taken by this study uses secondary data and primary data withannual time series data from 2013 to 2018. The data source is obtained from theBanjarmasin City Financial Board. This research uses quantitative descriptivemethods.The results of this study is that the rate of tax growth in restaurants inBanjarmasin City has an average of 14.17% which is categorized as less successful.For the calculation of restaurant tax contributions, the city of Banjarmasin has anaverage of 14.04% which means it is still not contributing. In contrast, from therestaurant tax effectiveness, the town of Banjarmasin has an average of 109.13%which can be categorized very effectively.